Płeć psychologiczna a asertywność w bliskich związkach = Psychological gender and assertiveness in close relationships - Kuczyńska, Alicja (1952- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the research was to answer three research questions. The first referred to the frequency with which women and men in close relationships are assertive towards each other, the second was connected with discovering the role of psychological gender in this type of behaviour, and the third was about the consequences of such behaviour on the level of satisfaction with an intimate relation. The research comprised 60 couples (120 individuals).
Keywords: płeć; płeć psychologiczna; relacje; asertywność; relationships; gender; psychological gender; assertiveness